Testing the relationships of hope and negotiable fate with sleep quality among university students in Hong Kong - Chan, Hok I.; Feldman, David B.; Shu, Tse-Mei (Frontiers in Psychology, 2025)
For university students, who are often under significant stress to perform well, sleep is particularly important, playing roles in learning and academic performance. Research demonstrates a relationship between hope and sleep quality. However, most work concerns Western samples, and the hope construct has been criticized for a Western bias. No research investigates sleep quality’s relationship to “negotiable fate,” a construct more relevant to Asian cultures. Whereas hope involves the individualistic expectancy that goals are achievable through personal action, negotiable fate involves the more collectivist-informed belief that control can be exercised over goals within limits of fate (family, community, society, other external factors). We investigated the relationship of hope and negotiable fate with sleep quality in 160 university students in Hong Kong, administering measures of hope, negotiable fate, sleep quality, depression, anxiety, stress, and life satisfaction. Lower hope was associated with poorer self-reported sleep quality. In addition, consistent with past research, mental health variables (particularly stress) accounted for significant variance in this relationship. Negotiable fate, however, did not relate to sleep quality.